Types and hydrogeologic features of surface and groundwater interactions in Uzbekistan - Kazbekov, Jusipbek S.; Rakhmatullaev, Shavkat A.; Huneau, Frederic; Le Coustumer, Philippe (2007)
The degradation of groundwater quality and quantity in Uzbekistan is a major problem for people in charge of drinking water supply. In order to guaranty a safe and effective access to the resource, it is necessary to estimate the quality of the resource and to evaluate the recharge rate and the residence time of water within the aquifer systems. This study presents a few attempts carried out to draw a first portrait of the real situation in Central Asia.